Perbedaan Struktur Morfologi, Anatomi, Fisiologi, dan Kandungan Fitokimia Daun Aur-Aur (Commelina Diffusa) pada Intensitas Cahaya Berbeda di Embung Leuwi Padjadjaran - Seviana Esti Handayani; Rusdi Hasan; Asep Zainal Mutaqin (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Commelina diffusa (family Commelinaceae) contains various secondary metabolites with potential antimicrobial and antioxidant properties. The production of these compounds is influenced by environmental factors, exceptionally light intensity, which also plays a role in determining the plant’s morphological and anatomical characteristics. This study aims to analyze differences in leaf morphology, stomatal anatomical structure, chlorophyll content, and phytochemical compounds in C. diffusa leaves growing in two locations with different light conditions at Embung Leuwi Padjadjaran, Sumedang. A descriptive method was used to examine leaf morphology, stomatal anatomy, chlorophyll content, and phytochemical compounds of C. diffusa in shaded and unshaded locations. The results showed that leaf morphology was relatively similar in both locations, but the leaf surface area was more significant in unshaded conditions (8,33 cm²). The stomata were hexacytic type with higher stomatal density in the shaded condition (591,082 cell/mm²) and a higher chlorophyll content (37,73 CCI). The result of Phytochemical analysis confirmed the presence of alkaloids, flavonoids, saponins, tannins, and quinones, which were relatively higher in unshaded conditions.